Development of a questionnaire for assessing factors predicting blood donation among university students: a pilot study - Jalalian, Mehrdad; Abd Latiff, Latiffah; Syed Hassan, Syed Tajuddin; Hanachi, Hanachi; Othman, Mohamed (2010)
University students are a target group for blood donor programs. To develop a blood donation culture among university students, it is important to identify factors used to predict their intent to donate blood. This study attempted to develop a valid and reliable measurement tool to be employed in assessing variables in a blood donation behavior model based on the Theory of Planned Behavior (TPB), a commonly used theoretical foundation for social psychology studies. We employed an elicitation study, in which we determined the commonly held behavioral and normative beliefs about blood donation. We used the results of the elicitation study and a standard format for creating questionnaire items for all constructs of the TPB model to prepare the first draft of the measurement tool. After piloting the questionnaire, we prepared the final draft of the questionnaire to be used in our main study. Examination of internal consistency using Chronbach's alpha coefficient and item-total statistics indicated the constructs "In-tention" and "Self efficacy" had the highest reliability. Removing one item from each of the constructs, "Attitude," "Subjective norm," "Self efficacy," or "Behav-ioral beliefs", can considerably increase the reliability of the measurement tool, however, such action is controversial, especially for the variables "attitude" and "subjective norm." We consider all the items of our first draft questionnaire in our main study to make it a reliable measurement tool.